THE INFLUENCE OF RELIGIOSITY, RISK PERCEPTION, AND MOTIVATION ON STOCK AND CRYPTO INVESTMENT INTEREST IN BANDA ACEH WITH UNDERSTANDING AS A MODERATING VARIABLE - Naharudi, Izul; Ibrahim, Azharsyah; Amri, Khairul (Journal of Sharia Economics, 2025)
Public interest in investment, particularly in stocks and cryptocurrencies, remains relatively low compared to Indonesia's large population. However, these two instruments have attractive profit potential. Therefore, this study aims to analyze the influence of religiosity, risk perception, and motivation on investment interest in stocks and crypto in Banda Aceh, with understanding as a moderating variable. This study employs a quantitative approach using a survey method involving Banda Aceh residents as respondents. Data was collected through questionnaires and analyzed using a moderation regression technique with the assistance of Smart-PLS 4. The results indicate that religiosity does not positively affect investment interest in stocks and crypto, with a t-statistic value of (0.880) < 1.96 and a p-value of (0.379) > 0.05. In contrast, risk perception has been proven to have a positive effect, with a t-statistic value of (2.711) > 1.96 and a p-value of (0.007) < 0.05. Additionally, motivation also positively influences investment interest, with a t-statistic value of (5.484) > 1.96 and a p-value of (0.000) < 0.05. Furthermore, the understanding variable does not moderate the relationship between religiosity and investment interest. However, understanding is proven to moderate the relationship between risk perception and motivation with investment interest, where individuals with better understanding tend to have higher investment interest. These findings imply that increasing investment interest in society requires broader education on investment, especially regarding risk management and long-term benefits. Additionally, the development of the Islamic capital market and clearer regulations for crypto assets can serve as supporting factors for increasing investment participation in Banda Aceh. Keywords: Religiosity, Risk Perception, Motivation, Investment Interest, Understanding.